A Retrospective Analysis of Rituximab Treatment for B Cell Depletion in Different Pediatric Indications - Wennmann, Merlin; Kathemann, Simone; Kampmann, Kristina; Ohlsson, Sinja; Büscher, Anja; Holzinger, Dirk; Della Marina, Adela; Lainka, Elke (Frontiers in Pediatrics, 2021)
Background: Rituximab (RTX) is used in cancer therapy as well as in the treatment of autoimmune diseases and alloimmune responses after transplantation. It depletes the disease-causing B cells by binding to the CD (cluster of differentiation) 20 antigen. We evaluate different pediatric treatment protocols (via fixed treatment schedule, B cell- or symptom-controlled) and their therapeutic effects. Methods: Demographic information, clinical and laboratory characteristics, and special laboratory values such as immunoglobulin G (IgG), CD19 positive B cells and Epstein-Barr viral load were retrospectively analysed in children treated with RTX between 2008 and 2016. Results: Seventy-six patients aged 1 to 19 (median 13) years were treated with 259 RTX infusions. The spectrum of diseases was very heterogeneous. RTX led to a complete depletion of the B cells. The reconstitution time varied between patients and was dependent on the application schedule (median 11.8 months). Fourteen out of 27 (52%) patients developed hypogamma¬globulinaemia. The risk of IgG deficiency was 2.6 times higher in children under 4 years of age than in olderones. In the last group IgG deficiency developed in only 38% of the cases (n=8). Recurrent and severe infections were observed each in 11/72 (15%) patients. Treatment-related reactions occurred in 24/76 (32%) cases; however, treatment had to be discontinued in only 1 case. In 16/25 (76%), the Epstein-Barr viral load dropped below the detection limit after the first RTX infusion. Conclusion: RTX is an effective and well-tolerated drug for the treatment of oncological diseases as well as autoimmune and alloimmune conditions in children. B cell depletion and reconstitution varies both intra- und interindividually, suggesting that symptom-oriented and B cell-controlled therapy may be favorable. Treatment-related reactions, IgG deficiency and infections must be taken into account.